Autophagy in sepsis: Degradation into exhaustion?. Issue 7 (2nd July 2016) - Ho, Jeffery; Yu, Jun; Wong, Sunny H.; Zhang, Lin; Liu, Xiaodong; Wong, Wai T.; Leung, Czarina C. H.; Choi, Gordon; Wang, Maggie H. T.; Gin, Tony; Chan, Matthew T. V.; Wu, William K. K.
ABSTRACT: Autophagy is one of the innate immune defense mechanisms against microbial challenges. Previous in vitro and in vivo models of sepsis demonstrated that autophagy was activated initially in sepsis, followed by a subsequent phase of impairment. Autophagy modulation appears to be protective against multiple organ injuries in these murine sepsis models. This is achieved in part by preventing apoptosis, maintaining a balance between the productions of pro- and anti-inflammatory cytokines, and preserving mitochondrial functions. This article aims to discuss the role of autophagy in sepsis and the therapeutic potential of autophagy enhancers.